Perlindungan Hukum Terhadap Anak Penyandang Disabilitas yang Menjadi Korban Tindak Pidana Pemerkosaan dalam Perspektif Hukum Pidana Islam - Antoni; Rifqi Hidayat (CV. Doki Course and Training, 2024)
Children with disabilities receive special protection under the law. Especially for children with disabilities who are victims of rape. Therefore, this study focuses on the main problem on the form of legal protection for children with disabilities who are victims of rape and how the analysis of Islamic criminal law relates to this. This study aims to explore the form of legal protection for children with disabilities who are victims of rape, as well as to understand the perspective of Islamic criminal law on the case. The research method used is normative legal research with a descriptive analytical approach. Data were obtained through literature studies and analysis of related legal documents. Legal materials were collected by reviewing, recording, evaluating library materials, or searching via the internet and analyzing legal materials by interpreting the legal materials that had been processed. The results of the study indicate that legal protection for children with disabilities who are victims of rape includes the protection that has been explained in Article 5 paragraph (3) letter (a) of Law Number 8 of 2016 concerning Persons with Disabilities stating that children with disabilities have the right to receive special protection from discrimination, neglect, harassment, exploitation, and sexual violence. Then preventive and repressive protection. In addition, Islamic criminal law considers children with disabilities as victims whose rights must be protected, by providing punishments in accordance with justice.